SPEECH ACT ANALYSIS OF THE PARTICIPANTS’ SPEECHES IN THE STUDY OF THE U.S INSTITUTES (SUSI) PROGRAM - Sitti Adhila Suprihana; Noor Eka Chandra; Elsa Rosalina (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
Research related to speech acts in speeches is frequently conducted, particularly in the context of speeches delivered by political and prominent figures. However, speeches by international exchange program students receive less attention despite their potential impact to influence audiences. Moreover, this study investigates the types of illocutionary speech acts employed by 20 undergraduate participants who were part of the 2021 Study of the U.S. Institutes (SUSI). The theme of the analyzed speeches is "This I Believe." A descriptive-qualitative method was employed, with data collected through audio and video recordings, transcribed, and analyzed using Searle’s speech act theory. Based on the findings, it was discovered that the exchange students' speeches, which employed illocutionary speech actions including assertive, directive, commissive, and expressive, function to represent their cultural background and life experiences. In conclusion, the study demonstrates that SUSI participants predominantly relied on assertive illocutionary acts to articulate their personal beliefs and values in their "This I Believe" speeches. This analysis highlights the importance of understanding the types of speech acts in different contexts, as they reveal the underlying intentions and strategies of the speakers in conveying their messages.